Pengaruh Kepuasan Kerja terhadap Kinerja Karyawan pada PT Cakrawala Citramega Multifinance Kota Palembang - Rosa Pratiwi; Muhammad Yusuf; Rini Rini (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
With this research, researchers have a goal of knowing job satisfaction on employee performance at PT CCM Palembang City. Research method is quantitative with a total of 35 employees as respondents using a simple linear regression analysis technique. Data collection techniques through interviews and questionnaires. Based on the research conclusions, job satisfaction at PT CCM Palembang City has a positive effect with a Tcount = 6.725 > Ttable = 1.690 and a significant value of 0.00 <0.05 and shows an R Square number of 0.565 on employee performance. The simple linear regression equation yields Y = 14.644 + 0.572X, indicating that job satisfaction at PT Cakrawala Citramega Multifinance Palembang City has a positive and significant effect on employee performance. Keywords: satisfaction, performance, employee